Contribution of Pancasila Learner Profile and Mathematics Learning Achievement to Critical Thinking Ability of Ahmad Yani Integrated Islamic Elementary School Students in Malang - Naana, Tesya Mahdaniya Ode; Sudjimat, Dwi Agus; Kuncoro, Tri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
translator This research investigates the effectiveness of the independent curriculum with the Pancasila student profile in developing students' critical thinking skills in Indonesia. His background emphasizes the importance of preparing students with relevant competencies for today's needs. Quantitative methods were used by collecting data through tests and questionnaires on SDIT Ahmad Yani students in Malang. The results of data analysis show that overall, the Pancasila student profile and mathematics learning achievement make a significant contribution to students' critical thinking abilities. Simultaneously, these two variables together explain around 24.1% of the variation in students' critical thinking abilities. Individually, the Pancasila student profile and mathematics learning achievement each make a significant contribution to students' critical thinking abilities. The conclusion of this research confirms that an approach using the Pancasila student profile and increasing mathematics learning achievement can help in developing students' critical thinking skills at school. Suggestions for this research include further intervention development based on these findings as well as comparative research to test the generalizability of these results to broader school populations with similar or different characteristics. This research provides important insights for curriculum and education development in Indonesia, especially in strengthening aspects of critical thinking skills as an integral part of Pancasila education.